2014
DOI: 10.1016/j.cmet.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones and the Promise of Insulin Sensitization in Type 2 Diabetes

Abstract: Type 2 diabetes is caused by insulin resistance coupled with an inability to produce enough insulin to control blood glucose, and thiazolidinediones (TZDs) are the only current antidiabetic agents that function primarily by increasing insulin sensitivity. However, despite clear benefits in glycemic control, this class of drugs has recently fallen into disuse due to concerns over side effects and adverse events. Here we review the clinical data and attempt to balance the benefits and risks of TZD therapy. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
372
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(384 citation statements)
references
References 197 publications
(211 reference statements)
8
372
1
3
Order By: Relevance
“…Contrary to our hypothesis, previous preclinical evidence and data from our in vitro experiments in human primary adipocytes, cold-induced BAT glucose uptake decreased in response to pioglitazone treatment. This suggests that reduced BAT activity may contribute to the weight gain associated with pioglitazone and other TZDs [26] previously attributed to proliferation and differentiation of subcutaneous white adipocytes, increased insulin sensitivity and fluid retention [9,27]. In this context, pioglitazone-induced BAT dysregulation could be counteractive and potentially worsen obesity-related comorbidities.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Contrary to our hypothesis, previous preclinical evidence and data from our in vitro experiments in human primary adipocytes, cold-induced BAT glucose uptake decreased in response to pioglitazone treatment. This suggests that reduced BAT activity may contribute to the weight gain associated with pioglitazone and other TZDs [26] previously attributed to proliferation and differentiation of subcutaneous white adipocytes, increased insulin sensitivity and fluid retention [9,27]. In this context, pioglitazone-induced BAT dysregulation could be counteractive and potentially worsen obesity-related comorbidities.…”
Section: Discussionmentioning
confidence: 94%
“…By activating peroxisome proliferator-activated receptor γ (PPARγ) in adipocytes, thiazolidinediones (TZDs) promote adipocyte differentiation, adipogenesis and browning [9]. TZDs are also putatively the only exogenous agents that have been conclusively demonstrated to induce browning of adipose tissue, although this has yet to be determined in humans in vivo [10].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In adipocytes, the PPARγ activity regulates the expression of genes involved in lipid metabolism, [5][6][7] in addition to the control of the expression of proteins involved in the uptake of lipids by adipocytes. 8 The PPARγ activation in adipose tissue presents an indirect activity in tissues which respond to insulin. 9 This effect was demonstrated using the drug rosiglitazone, a known PPARγ activator, in an experiment that showed that the drug is capable of increasing the insulin sensitivity of mice with severe insulin resistance but had no effect in mice with absence of adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…22. Although there are beneficial effects attributed to PPARγ agonism, a series of PPARγ‐knockout studies have clearly shown that the side effects that limit the use of pioglitazone and rosiglitazone are driven by PPARγ 23, 24. Until recently, it has been less well appreciated that all active TZDs also attenuate mitochondrial pyruvate uptake through the MPC2 in a manner that is separable from their PPARγ agonist activity 25.…”
mentioning
confidence: 99%
“…which limits doses that can be taken to the clinic 25. We and others have hypothesized that there may be a beneficial TZD pharmacology that is separable from PPARγ agonism and that this realization could change the drug discovery approach for the treatment of metabolic diseases 23, 24. Recent data point to the modification of pyruvate metabolism as a site of this pharmacology.…”
mentioning
confidence: 99%